A Spatiotemporal Multiscale Analysis of Runoff and Erosion in a Mediterranean Marly Catchment. Issue 12 (16th November 2017) - Inoubli, Nesrine; Raclot, Damien; Mekki, Insaf; Moussa, Roger; Le Bissonnais, Yves
Abstract : Core Ideas: Runoff and erosion were continuously monitored for 7 yr at four nested spatial scales. A small number of runoff and erosive events were very important. There was a seasonal time lag between runoff and erosive response due to shrink–swell processes. Topsoil erosion processes and high hydro‐erosive connectivity were predominant. A simple linear model explained mean annual erosion rates between spatial scales. An intensive monitoring investigation was conducted within the Kamech catchment (Cape Bon, Tunisia) to document the effect of scale on the hydrological and erosive responses in a Mediterranean climate regime with cracking soils. An evaluation of the individual contribution of topsoil and gully processes to total sediment delivery at different spatial scales was also conducted. Continuous runoff and erosion measurements during a 7‐yr period at four nested gauging stations were examined in a plot (P1; 1.32 ha), a plot + gully (P2+G; 1.37 ha), a micro‐catchment (MC; 15.2 ha), and the entire catchment (C; 263 ha). Data analysis showed a high interannual variability and contribution of only a few events; three major events generated approximately 20% of the total runoff and at least 50% of the total erosion at all of the monitoring stations. The results also highlight the strong seasonal dynamics of both water and sediment delivery, with a time lag observed between runoff and sediment responses. The presence of open cracks in autumn was identified as a main factor explaining this time lag. A constant monthly and annual specific runoff response was observed among the stations, and a simple linear model combining a single rate of topsoil (17 t ha −1 yr −1 ) and gully (80 t ha −1 yr −1 ) erosion (weighted by their contribution area) successfully predicted the differences observed in the mean annual erosion rates among the stations. Finally, this work showed the predominance of topsoil erosion processes in a Mediterranean catchment that is characterized by cracking soils and very high hydro‐sedimentary connectivity.